Notes about Racist Argentina and a Class-based Government - Perelman, Mariano Daniel (2017)
This essay deals with three things: - the  discusses the race-class nexus, a second that discusses the Macri election and government, and a third that suggests we think not just about economics but also about what it means to live a life with dignity.